THE KNOWLEDGE CONTINUUM: LITERATURE-BASED STUDY AS A RESEARCH TOOL IN SOCIAL SCIENCES - S, Dr.Uma.; Joanna Finny, Maureen; M, Dr. Nirmala; Hermansyah, Dr. Sam (Prodi Pendidikan Bahasa Inggris, FKIP, LP3M Universitas Muhammadiyah Sidenreng Rappang, 2025)
Literature-based research plays a vital role in the social sciences by systematically gathering, reviewing, and synthesising existing theories, empirical studies, and methodologies. This approach strengthens the development of conceptual frameworks, identifies research gaps, and integrates scattered findings into cohesive insights. Rather than serving as a routine academic requirement, literature reviews should function as analytical and interpretative processes that foster critical thinking. This paper highlights the importance of structured selection criteria, diversity in academic perspectives, and clear synthesis techniques to enhance credibility and depth. Challenges such as selection bias, resource limitations, and overreliance on secondary sources are addressed, along with strategies to overcome them. Ultimately, literature-based research emerges as a creative and active process that both preserves the intellectual heritage of the discipline and informs future scholarly directions.